Descriptive epidemiology of muscle-strengthening activities in Japanese middle-aged and older adults: the Hisayama Study - Jun Hata; Toshiharu Ninomiya; Takanari Kitazono; Takanori Honda; Mao Shibata; Satoko Sakata; Emi Oishi; Yoshihiko Furuta (BMJ Publishing Group, 2024)
Introduction Data on the prevalence of muscle-strengthening activities in Asia have been limited. Using data from a community-based cross-sectional survey of a general adult population in Japan, whose age and occupational distribution were very similar to the national averages, we aimed to estimate the prevalence of muscle-strengthening activities.Methods A community survey of local residents over 40 years of age was conducted in 2017-2018 as part of the Hisayama Study. Information on muscle-strengthening activities was obtained by means of a face-to-face interview by nurses. The prevalence of muscle-strengthening activities according to sex and age groups was estimated using a modified Poisson regression model. The prevalence ratios by subgroups based on anthropometry, physical conditions and lifestyle and behavioural factors were also estimated.Results Data on muscle-strengthening activities were available on 1509 men and 1946 women. Overall, 162 individuals (4.7%) engaged in muscle-strengthening activities at least 1 day/week, and 133 (3.8%) did so for 2 days or more per week. Women were less likely to engage in muscle-strengthening activities than men. The prevalence was generally comparable across subgroups of covariates, while an even lower prevalence was observed for some specific subpopulations, including individuals with diabetes and current smokers.Conclusions The prevalence of muscle-strengthening activities was estimated to be low in a general Japanese adult population. Population-wide approaches for the entire country and tailored educational interventions for specific subpopulations may be necessary in order to effectively enhance the participation in muscle-strengthening activities at a population level.